Large variations in antioxidant capacity and contents of Hungarian sour and sweet cherry cultivars - Papp, N.; Nyéki, J.; Szabó, Z.; Stefanovits-Bányai, É.; Szabó, T.; Hegedűs, A. (International Journal of Horticultural Science, 2010)
Sour cherry (Prunus cerasus L.) cultivars grown in Hungary are of local origin while most sweet cherry cultivars in Hungary are introduced from other countries.A great phenotypic variability is displayed by both species. In the present study, we analyzed 10 sour and 9 sweet cherry cultivars for their antioxidant capacity, total polyphenolics (TPC) and total anthocyanin (TMAC) contents. In general, sour cherries showed higher levels of antioxidant capacity, TPC and TMAC. The anthocyanin contents varied from 0.16 to 6.85 and 1.41 to 127.56 mg/100 g for sweet and sour cherries, respectively. However, TMAC generally seems to have a limited influence on the antioxidant capacity of cherries.An amarelletype sour cherry, ‘Pipacs 1’ showed the highest antioxidant capacity (21.21mmolAA/l) and TPC (44.07mgGA/l) in contrast to its lowanthocyanin content. The detected diversity presents a choice that can satisfy different consumer preferences, and meet specific nutritional requirements.